What happens when you write? Interrelation of linguistic modes as a methodological proposal for the study of writing - Alfonso López Corral; Pedro Rey Murrieta; Karla Acuña Meléndrez; Miriam Yerith Jiménez (Mexican Journal of Behavior Analysis, 2024)
The intricate nature of the writing phenomenon often creates the appearance of an inscrutable event. Various disciplines dealing with this phenomenon have asked questions such as: what is writing? Why and for what purpose do we write? Psychology has offered answers to such questions, adapting their formulation according to the theoretical position in question. The present work has the purpose of offering an answer to the question "what happens when writing?". For this purpose, writing psychological models (cognitive and behavioral) are reviewed and the concepts that support this paper are detailed: linguistic modes and linguistic enabling. We also discuss the possibility of studying the extent of the writing episode, as well as the connection between different writing episodes, through the concept of alternation of linguistic modes. Finally, we outline some characteristics of a task or experimental situation that allows the empirical evaluation of different degrees of molar-molecularity of writing, as an activity extensible in time and space that can be segmented into multiple interrelated episodes.